Simulation of the loss-cone instability in spherical systems: II. Dominating Keplerian potential - Polyachenko, Evgeny V.; Just, Andreas (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. According to our previous theoretical findings, physical processes in centres of galaxies, star clusters, and the Oort comet cloud can be significant